Heterotypic piRNA Ping-Pong Requires Qin, a Protein with Both E3 ligase and Tudor Domains - Zhang, Zhao (2011)
piRNAs guide PIWI proteins to silence transposons in animal germ cells. Reciprocal cycles of piRNA-directed RNA cleavage—catalyzed by the PIWI proteins Aubergine (Aub) and Argonaute3 (Ago3) in Drosophila melanogaster—expand the population of antisense piRNAs in response to transposon expression, a process called the Ping-Pong cycle. Heterotypic Ping-Pong between Aub and Ago3 ensures that antisense piRNAs predominate. We show that qin, a piRNA pathway gene whose protein product contains both E3 ligase and Tudor domains, co-localizes with Aub and Ago3 in nuage, a perinuclear structure implicated in transposon silencing. In qin mutants, less Ago3 binds Aub, futile Aub:Aub homotypic Ping-Pong prevails, antisense piRNAs decrease, many families of mobile genetic elements are reactivated, and DNA damage accumulates in nurse cells and oocytes. We propose that Qin enforces heterotypic Ping-Pong between Aub and Ago3, ensuring that transposons are silenced and maintaining the integrity of the germline genome.